Statistical study of cascade hydrodynamics and cavitation dynamics in propulsion pumps - Guoshou Zhao; Heng Liu; Rui Wu; Ning Liang; Linlin Cao (International Journal of Naval Architecture and Ocean Engineering)
The propulsion pump is widely employed in ocean engineering to generate thrust for surface or underwater vehicles. The cascade provides a simplified way to investigate the flow dynamics inside a propulsion pump considering specific parameters such as solidity and blade stagger. This work develops the foil generation method by in-house code through parametrically controlling the maximum and its position of camber and thickness, the influence of which on the performance obtained by numerical simulation is studied by the multiple statistical regression covering linear and interaction terms. For isolated hydrofoils, the interaction of maximum thickness and its position plays a major role in determining the performance. For cascade configurations with variable foils, besides the thickness interaction terms, other terms influencing lift and drag are not unified for different angles of attack. The solidity insignificantly affects the regression terms. For the cascade with the fixed foils, the solidity, axial velocity, and incidence angle all have an impact on the cascade foil's performance. The statistical loading distributions show that the isolated foil is a typical head-loading type, and the cascade foil is a body-loading type. The cascade cavitation dynamics indicate that a higher solidity and incidence angle would depress the cavitation development owing to the adjacent foil interference. This research aims to provide an instructive guide on pump blade design.